Disruptive Innovation & Chance for Latecomer Firms in E-Commerce: The Cases of the YES and PINDUODUO - Vananh Phamthi; Trung Ngominh (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2022)
The e-commerce market is considered one of the potential but fully competitive markets. However, it is also clear that gap-filling or market-dominating is a never-ending process in the e-commerce market. For this reason, this is one of the amazing playgrounds attracting many participants. The question is How and by which latecomer firms can enter and succeed in the existing e-commerce market. Therefore, this paper analyses the chances for latecomer enterprises to enter the competitive e-commerce market. To pursue this goal, the paper will analyze the role of the disruptive innovation theory and its e-commerce applications. The results reveal that applying disruptive business-model innovation is a better way for fledgling e-commerce brands to enter the existing market and succeed in competing with incumbents. Furthermore, the case of THE YES - a women's fashion e-commerce platform, and Pinduoduo - a Chinese largest agriculture-focused technology platform, are also analyzed as practical cases to join the research's results.
Keywords: O31; M13; 330; E-commerce; disruptive innovation; business-model innovation; latecomer firms